Evolution Semantics Of The Novelist Language Ibrahim Nasr Allah (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research sets out a window in which we look at to discuss vocabularies which concepts developed from the old dictionary into new meanings. The book binding of the Jordanian novelist: Ibrahim Nasr Allah who simplified his novels and made his poetry fertilized and meaningful.The scholar followed vocabularies and recognize their origins and meanings, approaching the concepts development. On the other hand, he observed what happened and changed in the area of the modern concepts.And the searcher sees that the arrangement of importance in the preoccupation with the practical side, in the process following vocabularies in literary novels poetry and divans, and inquest to success to reach the aim of study, the researcher follows the way. Baptized to stand on the most important aspects of semantic evolution of the term.